2018
DOI: 10.1021/acsanm.8b00730
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Reduced Graphene Oxide Wrapped Circular Au Nanoplatelets: Enhanced Photoluminescence, Excellent Surface-Enhanced Raman Scattering, Photocatalytic Water Splitting, and Non-Enzymatic Biosensor

Abstract: Herein, we demonstrate the synthesis and multifunctional properties of reduced graphene oxide (RGO)-wrapped Au nanoplatelets. We have characterized the sample by field emission scanning electron microscope (FESEM), high-resolution transmission electron microscope (HRTEM), energy-dispersive X-ray spectroscopy (EDS), high-angle annular dark-field scanning transmission electron microscopy (STEM-HAADF), electron energy-loss spectroscopy (EELS), and X-ray photoelectron spectroscopy (XPS) studies. It has been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…Nano-/micro-sized materials have created major interest due to their wide variety of potential applications (Majumder et al, 2015a(Majumder et al, , 2015b(Majumder et al, , 2016(Majumder et al, , 2018a(Majumder et al, , 2018bPal et al, 2018). Energy-related issues have attracted a good deal of attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-/micro-sized materials have created major interest due to their wide variety of potential applications (Majumder et al, 2015a(Majumder et al, , 2015b(Majumder et al, , 2016(Majumder et al, , 2018a(Majumder et al, , 2018bPal et al, 2018). Energy-related issues have attracted a good deal of attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Majumder et al found that the circular gold nanosheets coated with multifunctional reduced graphene oxide greatly enhanced the photoluminescence emission intensity caused by the common wobble of SPR and the fluorescence resonance energy transfer effect through the enhancement of Raman spectrum intensity. [205] Thus, under visible light irradiation, photocurrent flows through the sample to show the photocatalytic decomposition of water, indicating that it has great potential in the detection of nonenzymatic H 2 O 2 and ascorbic acid.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…On a wider note, there are three ways to improve the interfacial contact between the electrolyte and the electrode: (1) configuring a porous structure into the graphene derived composites by etching holes into the structure; (2) improving the electrolyte wettability of the same by altering its configuration by introducing functional groups or defects, heteroatom doping onto the planes of graphene, etc; and (3) Altering the graphene component's course in the composites. [ 43 ] Various graphene covered composites like graphene covered particles, [ 72 ] hollow spheres, [ 73 ] nanoplatelets, [ 74 ] and nanowires have been engineered for EES. Substantial specific surface area, higher magnitude of the packing density of active materials, optimized electrode thickness, high pore connectivity, and ionic conductivity are the major features that would result in supercapacitors with high energy density.…”
Section: Graphene‐based Products As Supercapacitor Electrode Materialsmentioning
confidence: 99%
“…Substantial specific surface area, higher magnitude of the packing density of active materials, optimized electrode thickness, high pore connectivity, and ionic conductivity are the major features that would result in supercapacitors with high energy density. [ 74 ] However, some of the criteria are contradictory to one another, thereby making the optimization process a challenging one. For example, an increase in packing density would influence in reducing the ion accessibility and pore interconnectivity which in turn affects the value of specific capacitance and rate capability.…”
Section: Graphene‐based Products As Supercapacitor Electrode Materialsmentioning
confidence: 99%